Winda Lingo Parugoneit1 or Why Set the Bush [On] Fire? Fire and Victorian Aboriginal People on the Colonial Frontier. Issue 2 (3rd May 2016) - Cahir, Fred; McMaster, Sarah; Clark, Ian; Kerin, Rani; Wright, Wendy
Abstract : There is an ethnographic and historical record that, despite its paucity, can offer specific insight into various contextual matters (purpose, motivations, acknowledgement) relating to how and why fire was being used by Victorian Aboriginal people in the nineteenth century. This insight is essential to developing cross-culturally appropriate land and fire management strategies in the present and into the future. This article demonstrates the need for further research into historical accounts of Aboriginal burning in Victoria.